Anticholinergic burden and cognitive performance: Cross‐sectional results from the ELSA–Brasil study. (31st December 2021) - Medeiros dos Santos, Adriana Nancy; Brunoni, Andre R; Goulart, Alessandra C; Viana, Maria Carmen; Benseñor, Isabela; Lotufo, Paulo; Suemoto, Claudia Kimie
Abstract: Background: The use of multiple drugs with anticholinergic properties is common in older adults and it may lead to cumulative anticholinergic toxicity and increase the risk of cognitive impairment. We investigated the association between the Anticholinergic Cognitive Burden scale (ACB) and cognitive performance among middle‐aged and older Brazilian adults (35‐74 years). Method: In this cross‐sectional analysis of the Brazilian Longitudinal Study of Adult Health (ELSA‐Brasil), 13, 065 participants were included (mean age = 51. ± 8.9 years old, 55% female, 53% white). Anticholinergic Cognitive Burden (ACB) was calculated according to the medications in use. We investigated the association of ACB with a global cognitive z‐score and memory, verbal fluency (VF), and Trail Making Test z‐scores, using multiple linear regression models adjusted for sociodemographic and clinical variables. Result: 16% of the sample had an ACB score >0. ACB was associated with worse cognitive performance on the memory (β= ‐0.022, 95% Cl= ‐0.045, 0.001, p=0.056) and in the trail making test (β= ‐0.021, 95% Cl= ‐0.043, 0.000, p=0.054) after adjustment for confounders Conclusion: Anticholinergic burden was related to worse cognitive performance on the memory and trail making test in Brazilian participants.